Loneliness and repetitive negative thinking mediate the link between social health and cardiac distress in heart disease patients - Hamid Sharif-Nia; Alun C. Jackson; Safoura Salehi; Fateme Miraghai; Seyed Hamzeh Hosseini (Scientific Reports)
Abstract Cardiovascular diseases are the leading cause of mortality worldwide, contributing to one-third of global deaths. Beyond physical health, heart disease is associated with cardiac distress, an emotional response that can negatively impact recovery and well-being. Understanding the psychological and social mechanisms underlying cardiac distress is crucial for improving patient outcomes. This study examines how social health (social support and social isolation) influences cardiac distress, with loneliness and repetitive negative thinking as mediators. To evaluate a theoretical model linking social health to cardiac distress, mediated by loneliness and repetitive negative thinking in patients with heart disease. A cross-sectional, correlational study was conducted in 2024 with 400 cardiac patients from two hospitals and one private clinic in Amol, Iran. Participants completed validated questionnaires assessing cardiac distress, social support, social isolation, loneliness, and repetitive negative thinking. Structural equation modeling was used for data analysis. Social isolation (r = 0.47, p < 0.001) and repetitive negative thinking (r = 0.50, p < 0.001) were significantly associated with greater cardiac distress. Social support negatively predicted both loneliness (β = − 0.32, p < 0.001) and cardiac distress (β = − 0.25, p < 0.01). Indirect effects showed that social support reduced cardiac distress by decreasing loneliness and repetitive negative thinking (β = − 0.23, p < 0.01), while social isolation increased cardiac distress through its influence on loneliness and repetitive negative thinking (β = 0.18, p = 0.05). The model explained 47.4% of the variance in cardiac distress. These findings highlight the importance of social health in managing cardiac distress among heart disease patients. Strengthening social support may alleviate loneliness and reduce repetitive negative thinking, ultimately improving emotional well-being and health outcomes. Future research should explore targeted interventions addressing these psychosocial factors to effectively reduce cardiac distress.